Sustainable Palm Oil (Elaeis guineensis Jacq.) Agribusiness Development in Indonesia: An Integrated Model - Suardi, Tennisya Febriyanti; Sulistyowati, Lies; Noor, Trisna Insan; Setiawan, Iwan; Nainggolan, Mai Fernando (Jurnal Agrikultura, 2025)
The sustainability of palm oil agribusiness was a strategic issue that connected economic, social, and environmental aspects in its management. Plantation practices and the palm oil industry contributed significantly to national economic growth and farmer welfare, but in reality, this activity was often associated with deforestation, land degradation, and social conflict. The importance of integrating various aspects of sustainability with agribusiness as a system from farmer perceptions produced priority elements that needed to be prioritized. The purpose of this study was to analyze the determinants of sustainable palm oil agribusiness development. This study was designed using a quantitative method with a survey approach. The sampling technique used proportionate stratified random sampling with a total of 249 smallholder palm oil farmers as respondents. Data processing was carried out using the Partial Least Square (PLS) analysis tool approach. The results of the study showed that the evaluation of modeling findings highlighted a significant influence of farmer rationality on the performance of the agribusiness system and sustainable palm oil agribusiness, as well as a significant influence of the performance of the palm oil agribusiness system on sustainable palm oil agribusiness. Meanwhile, in reality, the test results showed that farmer characteristics did not have a significant influence on any variable. Furthermore, the level of sustainability of palm oil agribusiness was perceived by farmers as more important in order from the social, environmental, technological, and economic dimensions. There was a need for cooperation and support from various parties to achieve and improve the sustainability of palm oil agribusiness, both from the fulfillment of input, production, handling of results, marketing, and supporting services to ensure its sustainability.